THE REPRESENTATION OF COERSIVE POWER ON THE SMOKING WARNING MESSAGE IN PUBLIC SPACE - sri wahyuni (Widyariset, 2015)
The number of the cigarette smoker in Indonesian is rapidly increasing. Based on that fact, as the authority, government represents his power by issued smoking warning message. The message is set in cigarette packages and other public cigarette advertisements. The language in the message contains warning, irony , and intimidation about the danger of smoking. That language is the representation of coercive power that leads the subordinate doing what the authority said. This study discusses the use and the factor behind the coercive power in the language of smoking warning message. The theory uses in this study is critical discourse analysis, while the method is qualitative descriptive. The result shows there are four types of the representation of coercive power. Those four are warning, prohibition, prohibition along with the intimidation, and irony.